Peran kepercayaan merek, citra merek, dan celebrity endorsement terhadap loyalitas merek bedak tabur Wardah - Anggi Novitasari; Tatik Suryani (STIE Perbanas Surabaya, 2017)
The competition in Indonesia cosmetics industry is growing rapidly. Many brands of face powder available in the market have been popular and got a good qualityr. Wardah is one of halal cosmetics manufactured in Indonesia. This study aims to analyze the effect of brand trust, brand image, and Celebrity Endorsement on brand loyalty of Wardah face powder in Surabaya. Data collected with questionnaire which given to 97 respondents from community of Surabaya. The sample was selected by judgement sampling. The data were alanized by using MRA (Multiple Regression Analysis). The results found that brand trust has significant effect on brand loyalty. Brand image has no significant effect on brand loyalty and Celebrity Endorsement has no significant effect on brand loyalty. The results show that brand trust, brand image and Celebrity Endorsement effect signifi-cantly on brand loyalty. The implication is to improve the brand trust by holding event beauty class for consumert to get more trust in the facial powderof Wardah, and to in-crease the service for the consumers and adjust the price for them.